Dampak Perkawinan Campuran Terhadap Harta Kekayaan Pasangan Suami Istri - Elsa Siffa Nabillah Nurlailatri; Printa Dewi Uma Azzahra; Dina Prihastuti; Reinhart Sebastian Pakasy; Nimas Calista Anggita; Vektor Setya Adi. P (Jurnal Hukum dan Sosial Politik, 2023)
Marriage is a sacred bond entered into by a man and woman to continue their lives. According to Law No. 1 of 1974, the definition of marriage is a spiritual and physical bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family in accordance with the belief in the Almighty God. A legal marriage is carried out according to the religious law and the state law of both parties. However, it does not rule out the possibility of a mixed marriage where the nationality of both parties is different. In this writing, we discuss a mixed marriage regarding the legal consequences of mixed marriages regulated in Law Number 1 of 1974 concerning marriage and discuss the mechanism for separating assets in mixed marriages according to Denpasar Court decision Number 536/Pdt.P/2015/PN.Dps. Based on this decision, both parties entered into a mixed marriage between Indonesian citizens and US citizens, but the two parties did not make a prenuptial agreement for the separation of their respective assets as a condition for carrying out a mixed marriage. In this case, even though a foreigner is married to an Indonesian citizen and has registered their marriage and lives in Indonesia, they still have limited rights to buy and sell immovable assets